Does Cosmetic Rhinoplasty Improve Self-Concept and Patient’s Satisfaction with Nose Fitness? Testing the Differences Before and After Surgery with 3 To 6 Months Follow-Up - Seyyed Vali-allah Mousavi (Caspian Journal of Neurological Sciences, 2016)
Background: Despite the great number of cosmetic rhinoplasties, ‌there are few studies on the improvement of self-concept and patient satisfaction with nose fitness.